Pengembangan Kawasan Industri Rotan di Desa Welahan, Kabupaten Jepara - Intan Muning Harjanti; Pratamaningtyas Anggraini (Jurusan Perencanaan Wilayah dan Kota, 2019)
Welahan Village is one of the village in Jepara District which has dominating industrial activities. Where people in the area doing industrial activities (home industry) by producing processed goods from rattan. However, the existence of these small rattan industries has not been massively packaged, which still seems to stand alone - without good planning and management. So, it is necessary to develop a rattan industrial area in Welahan Village, Jepara Regency. So that, later it can develop rattan industry activities and increase economic growth in this area. The purpose of this study is to determine the direction of development of rattan industrial areas in Welahan Village, Jepara Regency, by conducting non-physical analysis (activity and user analysis, space needs analysis, spatial relationship analysis, space organization) and zoning analysis. The results of this research are zoning of the rattan industrial area in Welahan Village, which consists of sports zones, service zones, processing zones, supporting zones, trade zones and services, supporting zones and green open space zones.